Behavior Modes and Attitudes of Hangzhou’s Bike-sharing Systems — Expected Utilities, Real Benefits and Perspective - W. W. Sun; X.L. Dai (International Association of Lowland Technology, 2016)
In the background of the bike-sharing program booming, this research carried an empirical investigation in Hangzhou, China to explore the usage pattern and attitude of different user groups. The actual benefits of this system were evaluated in the light of the expected utilities set up in the beginning and also data from other cities’ practices. By a methodological improvement on questionnaire sampling, it is found that besides the frequent user group, there are substantial amount of people who are occasional users or non-users. The latter two groups would be the target groups in the aim of enhancing the effectiveness of the system. By diagnosing the characteristics of the two target groups from the frequent user group in a statistic manner, the paper shed light on the efficient intervention arrangements what the governments should pay attention to. Also, by a comprehensive comparison of international cases, it is believed that although Hangzhou is already a leading city for bike-sharing program in China, there is substantial potential to improve it in terms of three indicators: average daily usage frequency, proportion of trips combined with public transportations, and proportion of trips converted from cars.